A Structural Equation Model Analysis of the Relationships Between Career Indecision, Sense of Control, Self-Efficacy, Rumination, and Depression in High School Students - Amaral, Fay; Henning, Marcus; Moir, Fiona; Krägeloh, Chris (Springer Science and Business Media LLC, 2024)
This study examined the links between career-decision making and mental health. Levels of career indecision, rumination, general self-efficacy, sense of control, and depression in 275 high school students were assessed. Anonymous responses to five valid and reliable scales were analysed using structural equation modelling. A conceptual model was postulated and tested for goodness of fit. The results yielded that perceived external constraints acted as a significant mediator between career indecision and depression. Ruminative brooding significantly moderated the link between career indecision and perceived external constraints. The structural equation analysis on the adjusted model demonstrated an overall good model fit. The study highlights the intricate linkages and effects between students’ career decision making, thinking patterns, perceptions of external barriers, and mental health. Levels of depression and career indecision are heightened in the present study. The mechanistic model and associated findings of the study support the necessity of providing targeted interventions for high school students that concurrently address mental health concerns alongside career-decision making, whilst also ameliorating problems associated with self-efficacy, perceived barriers, and negative thought patterns.